Pemberian Pupuk Nano NPK Organik Terhadap Hasil Bawang Merah - Endang Setyowati; Samanhudi Samanhudi; Muji Rahayu (Universitas Sebelas Maret, 2025)
The continuous use of chemical fertilizers can reduce nutrient absorption efficiency and contribute to gas emissions that trigger global warming. One solution to increase nutrient absorption efficiency is to use nano fertilizers. This study aims to evaluate the effect of organic NPK nano fertilizer application on shallot yield. The research was conducted using a completely randomized design (CRD) arranged in a factorial design, consisting of two treatment factors with 12 treatment combinations repeated three times. Fertilization of shallot plants by applying nano NPK fertilizers up to a dose of Nitrogen 220, Phosphorus 160, and Potassium 120 kg/ha can increase the growth variables of shallot plants. The best results were obtained in the Crok Kuning variety with nano fertilizer doses of Nitrogen 220, Phosphorus 160, Potassium 120 kg/ha, and the Tajuk variety with nano fertilizer doses of Nitrogen 160, Phosphorus 100, Potassium 60 kg/ha, which produced the optimal number of tubers. However, in both Crok Kuning and Tajuk varieties, the application of nano NPK fertilizers did not have a significant effect on plant fresh weight, leaf area index, specific leaf area, relative growth rate, tuber weight per plant, and tuber diameter. Further research can be conducted with the method of fertilizer application through the leaves and using different varieties.